Vancomycin Resistant Enterococcus - Mehveen Iqbal, SairaBugti,Sabiha Mirza, Muhammad Akbar Hassan, Mehveen Iqbal , SairaBugti ,Sabiha Mirza , Muhammad Akbar Hassan . (Journal of Rawalpindi Medical College, 2019)
Background: To study prevalence of Vancomycin resistant Enterococcus in different wards of hospital and associated risk factors. Methods:Samples were collected from different wards 110 positive samples were analyzed. To isolate the organism, samples were streaked on Blood and CLED medium and identified with specific colony characteristics and further confirmed by biochemical tests. Vancomycin drug sensitivity was performed on Mueller-Hinton agar plates by disc diffusion method. Results:Out of 110 Enterococcus positive samples 32% showed resistance to Vancomycin. E. faecalis(67%) was observed as frequently present organism followed by E. faecium (33%). Most of the VRE strains were isolated from patients admitted to ICU (54%), hospitalized for more than one week and were on antibiotics. Conclusion: Vancomycin resistant Enterococcus becomes an important issue for the health authorities. Lack of basic health necessities, unskilled medical staff and unnecessary medication are mentionable concerns, leading to the development of resistant strains.